\((x+y):(x-y), (x^2+y^2)\) \(:(x+y)^2\) এবং \((x^2-y^2)^2:(x^4-y^4)\) -এদের মিশ্র অনুপাত বা যৌগিক অনুপাত নির্ণয় করি
\((x+y):(x-y) ,(x^2+y^2 ) ∶(x+y)^2\)
এবং \((x^2-y^2 )^2 ∶(x^4-y^4 ) \) এর মিশ্র অনুপাতটি হল
\(=(x+y)×(x^2+y^2 )×(x^2-y^2 )^2 \) \(:
(x-y)×(x+y)^2×(x^4-y^4 )\)
\(=(x+y)(x^2+y^2 ) {(x+y)(x-y) }^2\) \(:
(x-y) (x+y)^2 (x^2+y^2 )(x^2-y^2 )\)
\(=(x+y)(x^2+y^2 ) {(x+y)(x-y) }^2\) \(:
(x-y) (x+y)^2 (x^2+y^2 )(x^2-y^2 )\)
\(=(x+y)(x^2+y^2 ) (x+y)^2 (x-y)^2\) \(:
(x-y) (x+y)^2 (x^2+y^2 )(x+y)(x-y)\)
\(=(x+y)^3 (x-y)^2 (x^2+y^2 )\) \(:
(x+y)^3 (x-y)^2 (x^2+y^2 )\)
\(=1:1\) (Answer)